2014
DOI: 10.1007/s10489-014-0574-5
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Support vector regression methodology for prediction of input displacement of adaptive compliant robotic gripper

Abstract: The prerequisite for new versatile grippers is the capability to locate and perceive protests in their surroundings. It is realized that automated controllers are profoundly nonlinear frameworks, and a faultless numerical model is hard to get, in this way making it troublesome to control utilizing tried and true procedure. Here, a design of an adaptive compliant gripper is presented. This design of the gripper has embedded sensors as part of its structure. The use of embedded sensors in a robot gripper gives t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The short-term wind speed sequence forecast results at point x i+11 each interval of 10 min given by GN-KRR [7,8,32], ν-SVR [33,34], and BN-KRR are illuminated with MAE, MAPE, RMSE, and SEP indicators are used to evaluate the prediction results of the three models at point x i+11 each interval of 10 min shown in Table 1. Table 1.…”
Section: Forecast Wind Speed At Point X I+11 Each Interval Of 10 Minmentioning
confidence: 99%
“…The short-term wind speed sequence forecast results at point x i+11 each interval of 10 min given by GN-KRR [7,8,32], ν-SVR [33,34], and BN-KRR are illuminated with MAE, MAPE, RMSE, and SEP indicators are used to evaluate the prediction results of the three models at point x i+11 each interval of 10 min shown in Table 1. Table 1.…”
Section: Forecast Wind Speed At Point X I+11 Each Interval Of 10 Minmentioning
confidence: 99%
“…The fundamental working principle of the SVM (support vector machine) is to implement the data-mapping in some other dot product spaces through a nonlinear mapping and develop the linear algorithm in the feature space [17].…”
Section: Support Vector Regressionmentioning
confidence: 99%
“…This successful forecasting technique, popular due to its superior generalization performance and fast convergence, is extended to identification and modelling of nonlinear systems using the support vector regression (SVR) [27]. With the appropriate kernel functions, SVR has been widely used as an artificial intelligent technique in many areas such as health monitoring [28], concrete strength prediction [29], robotics [30]. Taghavifar and Aref Mardani [31] applied SVR to model energy dissipation of runoff-road vehicles and found that they outperformed the popular ANN technique.…”
Section: Introductionmentioning
confidence: 99%